Case report: Histiocytic sarcoma as transdifferentiation of a marginal zone lymphoma—a case presentation based on post mortem examination and review of the literature - Jauch, Annaïse J.; Alborelli, Ilaria; Balestri, Ilaria; Krasniqi, Fatime; Tzankov, Alexandar; Kasenda, Benjamin; Menter, Thomas (Frontiers in Oncology, 2025)
BackgroundHistiocytic sarcoma (HS) is a rare and aggressive hematopoietic malignancy characterized by the proliferation of cells resembling mature histiocytes. It typically presents in extranodal sites such as the skin, the gastrointestinal tract, and soft tissues and is often accompanied by systemic symptoms including fever and weight loss. HS occurs de novo or results from transformation/transdifferentiation from other hematological neoplasms, such as low-grade B-cell lymphomas. To date, only four cases of HS arising from marginal zone lymphomas (MZL) have been documented.Case presentationWe describe a 66-year-old female patient who presented primarily with abdominal pain and constitutional symptoms. The clinical evaluation showed significant hepatosplenomegaly and lymphadenopathy. A liver biopsy demonstrated a sinus-associated spread of HS. The patient died of suspected hemorrhagic shock before the diagnostic results were finalized and before rescue treatment could be initiated. The autopsy findings confirmed a widespread metastatic HS and concurrent MZL. The molecular analysis showed that both neoplasmas were clonally related, supporting the hypothesis of transformation/transdifferentiation of MZL into HS.ConclusionWe have reported the fifth unusual transformation of a MZL into a HS. Transformed/transdifferentiated HS is a rare and aggressive neoplasm. Evidence from the published case reports suggests that its clinical course may be more severe than de novo HS. This underscores the importance of investigating rare presentations and considering the possibility of an underlying pre-existing hematological malignancy.